DESIGN AND SIMULATION OF THE PROCESS OF MAKING CERAMIC TILES MOLDUSING THE MASTERCAM X5 TO GENERATE G-CODE - Aa Santosa; Naufal Yosi Laksana (Universitas Majalengka, 2023)
ABSTRACTIn its development, every manufacturing industry increasingly makes people think more creatively and are faced with new problems, especially in making new innovations. The purpose of these production issues is to achieve faster and more efficient production targets. The metal machining process is an important factor to support the quality of the final product, but there is one obstacle that must be faced.Mold or Mold is a technology that is produced using software assistance to speed up work and make products better in terms of accuracy and effectiveness. The use of technology in the manufacture of products in various industrial fields continues to be developed in order to increase efficiency. This is also the case with the ceramics industry, which has been increasingly being used as a ceramicshousehold needs. In the production process, the ceramics industrygradually using automated processes to replace processesmanuals. The purpose of this study is to analyze the manufacture of ceramic mastersby using a CNC machine in the Kasongan ceramic industry. ResultsThis research is expected to be a reference in making ceramicsusing a CNC machine. Analysis of machining processes performedincludes machining parameters, time and yield or productThis research is an application of the CAD CAM course, the Mastercam software application is very helpful in mold making innovation. Tiles are a form of a product resulting from a metal molding process, the mold material is made of st 37 steel.